Developments in Polynesian Ethnology - Borofsky, Robert; Howard, S. Alan (University of Hawai'i Press, 1989)
Development in Polynesian Ethnology assesses the current state of anthropological research in Polynesia by examining the debates and issues that shape the discipline today. What have anthropologists achieved? What concerns now dominate discussion? Where is Polynesian anthropology headed? In a series of provocative and original essays, leading scholars examine prehistory, social organization, socialization and character development, mana and tapu, chieftainship, art and aesthetics, and early contact. Together these essays show how history, anthropology, and archaeology have combined to give a broad understanding of Polynesian societies developing over time--how they represent a blend of modernity and tradition, continuity and change. This book is both an introduction to Polynesia for interested students and a thought-provoking synthesis for scholars charting new directions and posing possibilities for future research. Scholars outside Polynesian studies will find the perspectives it offers important and its comprehensive bibliography an invaluable resource.